Metafunction in The Texts of Brochure - Nova Andriani (Departement of Mathematics Education, 2024)
The objective deals with Metafuction functions in the text of brochure. It based on qualitative descriptive research design. This objectives of the study were: (1) to describes the types of themes in the text of brochure and (2)to identify the social contexts in the text of brochure. This research applied qualitative descriptive to describe about data analysis. The qualitative analysis was applied in such away in order to find out theoretically related to the research question. The Source of data was the text of brochure which consists of 22 paragraphs. The sources was taken through document that is writtern in the text of brochure.The Theme is focused on Topical theme and there are 103 clauses of theme. The text was analyzed with the reference to theories of Systemic Functional Linguistic (SFL). The finding shows that the proportion are as ;(1) Marked Simple Theme is 53 %, (2) Marked Multiple Theme is 5%, (3) Unmarked Simple Theme is 41 % and the last (4) Unmarked Multiple Theme is can not found. It is concluded that the Marked Simple Theme are used in large number and Marked Multiple Theme are used in smaller number.